Myocardial Flow Reserve Measurement During CZT-SPECT Perfusion Imaging for Coronary Artery Disease Screening: Correlation With Clinical Findings and Invasive Coronary Angiography—The CFR-OR Study - Bailly, Matthieu; Thibault, Frédérique; Courtehoux, Maxime; Metrard, Gilles; Angoulvant, Denis; Ribeiro, Maria Joao (Frontiers in Medicine, 2021)
Purpose: The aim of this study was to assess the results of CZT-SPECT Myocardial flow reserve (MFR) in Coronary Artery Disease (CAD) screening regarding clinical risk and its correlation to Invasive Coronary Angiography (ICA). Methods: 137 patients (61 male, 76 female) referred for CAD screening Myocardial Perfusion Imaging (MPI) between November 2018 and April 2020 were included in the CFR-OR prospective trial. 10 years risk of cardiovascular death according to the European Society of Cardiology (SCORE) was calculated. SPECT one-day 99mTc-tetrofosmin protocol was acquired on CZT cardiac dedicated pinhole cameras. Low dose thoracic CT was used for coronary calcium score (CCS) evaluation. ICA when performed within 3 months was also analyzed. Results: Mean SCORE and mean global MFR were respectively 4 ± 3.1 % and 2.50 ± 0.74; 34 patients had impaired CFR (using a threshold of 2). There was a significant inverse correlation between MFR and SCORE (p=0.006), gender (p=0.019) and number of cardiovascular risk factors (p=0.01). MFR was significantly reduced in patients with CCS above 1 (p=0.01). No significant correlation was found between MFR and individual cardiovascular risk factors (dyslipidemia, hypertension, diabetes or family history of CAD). 23 patients underwent ICA. Global MFR SPECT sensitivity and specificity were 83.3% and 100 %, respectively with an Area Under Curve = 0.94. Conclusion: Adding MFR to SPECT MPI for CAD screening on CZT camera may contribute to high-risk patient identification and enhance diagnostic performances. MFR could help physician decision to perform ICA.